Correlation between physical performance and fatigue in cancer patients - Dimeo, F.; Stieglitz, R.-D.; Novelli-Fischer, U.; Fetscher, S.; Mertelsmann, R.; Keul, J. (Annals of oncology, 1997)
Background Fatigue and a reduction in physical ability are common and often severe problems of cancer patients regard less of disease stage and modality of treatment. However, while physical performance can be assessed objectively with laboratory tests, fatigue is a subjective phenomenon whose perception is influenced by past experience and expectations for the future. Patients and methods To evaluate the correlation between fatigue and physical impairment, we assessed maximal physical performance with a treadmill test, and mental state with two questionnaires, the Profile of Mood States (POMS) and the Symptom Check List (SCL-90-R), in a successive series of 78 cancer patients with solid tumors or hematological malignancies. Results A weak association between fatigue and maximal physical performance was found (r = −0.30; P < 0.01). How ever, intensity of fatigue showed a strong correlation with several indicators of psychological distress such as depression (r = 0.68), somatization (r = 0.64) and anxiety (r = 0.63; P for all <0.001). Furthermore, patients with lower levels of physical performance had significantly higher scores for depression (P = 0.005), somatization (P = 0.03) and anxiety (P = 0.08), and significantly lower scores for vigor (P = 0.05) than their counterparts whose physical performance was higher. Conclusions We conclude that fatigue in cancer patients may be related to mood disturbance but appears to be independent of physical performance. Moreover, low physical performance can be viewed as an independent predictor of mental distress in cancer patients.